Comprehensive Perception Approach of Adoption: Experimenting Hybrid Chinese Maize Varieties in Benin - DEDEHOUANOU, HOUINSOU; AFFOKPON, ANTOINE; SIKIROU, Rachidatou; AKISSOE, AZANDÉGBÉ SIMON; Chabi G., Yallou; Ahounou, Jean-Louis; Akondé, François-Xavier; BADOU, ANTOINE; Sagbohan, Jacqueline (My University, 2019)
The probability of adoption of four Chinese Hybrid Varieties of maize is considered as a favorable perception for these varieties by actors. In order to understand the way of adoption, a panel of actors comprising producers, processors, traders, extension officers, local elected representatives and, above all, end-users, was used as enumerator to evaluate the behavior of those varieties in comparison to the reference maize varieties known as “local” in experiment plots during the vegetative, harvesting and processing phases. For each actor surveyed and for each introduced variety, the comparative index of appreciation (IA) was determined by the difference in perception scores with respect to each of the descriptors evaluated. The adoption of maize varieties within the sites surveyed was affected by the respondent’ social profile (title), the number of varieties already adopted by the respondent, respondent’s experience, age, educational background, membership to an association/organization and the site (research station). The estimation of adoption relative to probabilities (odds ratio) of each variety of maize from the binary logistic regression models revealed only one variety having more than one in two chances for being adopted. Unlike the adoption rate of maize varieties calculated after expensive dissemination efforts, the analysis of probabilities and determinants of adoption somewhat reduces research, pre-extension and extension efforts. The proposed approach allows for a flexible integration of research experiments and field extension concerns of the process of adoption by creating panels of stakeholders around research experiments on research stations.
Keywords: adoption probability; adoption rate; maize; China; Benin